2020
DOI: 10.1155/2020/4598437
|View full text |Cite
|
Sign up to set email alerts
|

General, 21-Day Postoperative Rehabilitation Program Has Beneficial Effect on Oxidative Stress Markers in Patients after Total Hip or Knee Replacement

Abstract: Imbalance in prooxidant-antioxidant equilibrium plays an important role in the progression of osteoarthritis (OA). Postoperative rehabilitation significantly improves the functional activity of patients with OA. We aimed to assess the effect of the general 21-day postoperative rehabilitation on the oxidative stress markers in patients after total hip arthroplasty or knee replacement. Patients (n =41) started individually designed postoperative rehabilitation ca. 90 days after endoprosthesis implantation. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…Currently, knee and hip arthroplasty are taking up an increasing proportion of orthopedic surgery, and the demand especially from those patients mainly over 60 years old will continue to grow [ 1 , 2 ]. Evidence has indicated that postoperative delirium (POD) is a relatively common and serious complication in patients undergoing hip and knee arthroplasty, and the probability of occurrence is up to 17.6% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, knee and hip arthroplasty are taking up an increasing proportion of orthopedic surgery, and the demand especially from those patients mainly over 60 years old will continue to grow [ 1 , 2 ]. Evidence has indicated that postoperative delirium (POD) is a relatively common and serious complication in patients undergoing hip and knee arthroplasty, and the probability of occurrence is up to 17.6% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work presented the biochemical and morphological characteristics of the blood of patients before and after the 21-day general rehabilitation program [ 40 ]. Here, we assessed whether the biochemical parameters analyzed in the patients' serum changed compared to the laboratory norm [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Before starting and after completing the 21-day general rehabilitation program, each patient underwent the 6-minute walk test (6MWT) [ 44 ] to track changes in the patient's functional exercise capacity and assess the effectiveness of the rehabilitation program [ 45 , 46 ]. The results of the 6-minute walk test (6MWT) after a 21-day general rehabilitation in the studied patients were presented in Skrzep-Poloczek et al [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations